COMPARATIVE FIGURATIVE LANGUAGES IN SONG LYRICS SEPANJANG HIDUP OF MAHER ZAIN - SITI JAMZAROH (Balai Bahasa Sulawesi Tengah, 2019)
Abstract This study aims to describe how figurative language is used in the lyrics of the song